2021
DOI: 10.3389/fcell.2021.738341
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Promote Extracellular Matrix Component Remodeling by Activating YAP in Human Retinal Capillary Endothelial Cells

Abstract: Remodeling of extracellular matrix (ECM) components of endothelial cells is the main cause of retinal vascular basement membrane (BM) thickening, which leads to the initiation and perpetuation of microvasculopathy of diabetic retinopathy (DR). Excessive amounts of glucocorticoids (GCs) are related to the presence and severity of DR, however transcriptional effects of GCs on the biology of human retinal capillary endothelial cells (HRCECs) and its impacts on DR are still unclear. Here, we showed that GC (hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“… 248 , 249 Intraocular glucocorticoid injection is often used to treat persistent and refractory diabetic macular edema, which improves vision but increases the incidence of cataracts and glaucoma. 250 Drugs such as ranibizumab, aflibercept, and fenofibrate have been included in clinical trials to evaluate their effectiveness and safety (Table 3 ), thus providing new ideas for treating DR.…”
Section: Introductionmentioning
confidence: 99%
“… 248 , 249 Intraocular glucocorticoid injection is often used to treat persistent and refractory diabetic macular edema, which improves vision but increases the incidence of cataracts and glaucoma. 250 Drugs such as ranibizumab, aflibercept, and fenofibrate have been included in clinical trials to evaluate their effectiveness and safety (Table 3 ), thus providing new ideas for treating DR.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF receptor activation inhibits LATS and activates YAP/TAZ to regulate VEGF‐induced retinal angiogenesis 48 . Several medications, such as the Chinese patent medicine Compound Xueshuantong Capsule, 23,52 folic acid 47 and glucocorticoids, 53,54 reverse retinal vascular dysfunction by inhibiting the YAP/TAZ pathway, thereby ameliorating diabetic macular edema and reducing the incidence of complications. These results suggest that YAP/TAZ may be a potential therapeutic target for DR.…”
Section: Hippo Signalling Pathway In Eye Diseasesmentioning
confidence: 99%
“…Recent studies have shown that YAP/TAZ signaling plays an important role in glaucoma-related ocular tissues including the lamina cribrosa, 67 retinal capillary endothelial cells, 68 and TM. 69–71 The cross-talk between YAP/TAZ and GR signaling in the TM may contribute to GIOHT/GIG.…”
Section: Basic Science Review Of Gig/giohtmentioning
confidence: 99%